Analysis of Serum Th1/Th2 Cytokine Levels in Patients with Acute Mumps Infection - Malaiyan, Jeevan (J Glob Infect Dis, 2016)
BACKGROUND: The mumps virus is frequently the causative agent of parotitis. There has been no study on serum cytokine levels of acute mumps parotitis except for a few which document cytokine levels in cerebrospinal fluid of mumps meningitis. It is with this notion, our study aimed to find Th1/Th2 cytokine levels from patients with acute mumps parotitis. MATERIALS AND METHODS: Concentrations of mumps-specific IgM, mumps, measles, rubella-specific IgG antibody, and Th1/Th2 cytokines, namely interferon-γ (IFN-γ), interleukin-2 (IL-2), IL-4, and IL-10 were measured simultaneously in serum from 74 patients (42 pediatric and 32 adult cases), 40 healthy subjects (20 pediatric and 20 adults) and in the supernatant of peripheral blood mononuclear cells stimulated with mumps virus genotype C which served as the positive control. Statistical significance was analyzed between each group by means of Mann–Whitney U-test, Kruskal–Wallis test, and Spearman's rank correlation coefficient test. RESULTS: IgM positivity confirmed acute infection in all 74 patients and of these 67 were vaccinated cases; however, very few of them (10/67) were positive for mumps IgG. We found that IFN-γ, IL-2, and IL-10 showed a statistically significant increase in both pediatric and adult patients with acute mumps infection when compared to healthy controls and values were comparable to the positive control. CONCLUSION: The Th1 cells play important roles during the acute phase of mumps parotitis.